A new analytical procedure for solving the non-linear differential equation arising in the stretching sheet problem - Siddheshwar, Pradeep G.; Mahabaleswar, U.S.; Andersson, Helge (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses a new analytical procedure for solving the non-linear boundary layer equation arising in a linear stretching sheet problem involving a Newtonian/non-Newtonian liquid. On using a technique akin to perturbation the problem gives rise to a system of non-linear governing differential equations that are solved exactly. An analytical expression is obtained for the stream function and velocity as a function of the stretching parameters. The Clairaut equation is obtained on consideration of consistency and its solution is shown to be that of the stretching sheet boundary layer equation. The present study throws light on the analytical solution of a class of boundary layer equations arising in the stretching sheet problem.
Keywords: differential equations; Clairaut equation; Newtonian liquid; stretching sheet; suction/injection